Peran Mise-En-Scene Terhadap Proses Efikasi Diri Tokoh Chiron dalam Film Moonlight: The Role of Mise-en-scene to the Chiron Character Self-Efficacy Process in Moonlight Film - Rinaldo, Afrizal; Rozi, Romdhi Fatkhur; Ningrum, Rara Mustika (Universitas Jember, 2024)
Abstract This research discusses the role of mise-en-scene in the process of self-efficacy of Chiron's character in Moonlight. The purpose of this research is to describe the role of the mise-en-scene in the visual aspect of Chiron's self-efficacy process. The data of this study were studied using Bordwell and Thompson's mise-en-scene theory, as well as Albert Bandura's observational learning which focuses on aspects of mise-en-scene (settings, costumes and make-up, lighting, as well as characthers and their movements) and the four forming factors of selff efficacy (mastery of experience, social modeling, social persuasion, and physical and emotional conditions). The results of the data analysis conclude that there are eleven scenes with mise-en-scene aspects that support the formation of the chiron character's self-efficacy process in the three story stages. Social modeling, social persuasion, and physical and emotional conditions occur in the first to third stages, while mastery of experience only occurs in the third stage. Keywords: Moonlight Film, Mise-en-scene, Self efficacy